Aerial survey - Eltringham, S K (Wildfowl, 1960)
The first full season of aerial surveys conducted by the Wildfowl Trust was 1957-58. Much of the flying was exploratory and a large part of the funds set aside for this project was spent in visiting Canada to observe the aerial surveys carried out there by the U. S. Fish and Wildlife Service. With this experience behind us we hoped to establish the practicability of aerial surveys in this country on a firm basis in 1958-59. Unfortunately our efforts were seriously curtailed in the winter by the exceptional sequence of bad weather which allowed flying on only 50 of 151 days between November and March. However, about 158 flying hours were spent on survey in the twelve months from September 1958 to August 1959–a satisfactory total considering that flying did not begin until the end of November. The time was divided between a number of surveys which are considered in more detail below.